Nostril Advantage in Trigeminal/Olfactory Perception and Its Relation to Handedness. (March 2017) - Manescu, Simona; Daniel, Benjhyna; Filiou, Renée-Pier; Lepore, Franco; Frasnelli, Johannes
Introduction: Few studies investigated nostril-advantage in chemosensory perception, particularly, in relation to handedness. The aim of the present article was therefore to assess whether trigeminal/olfactory perception is altered by handedness. Methods: We tested 50 (all right-handed) and 43 (22 left-handed) participants in Studies 1 and 2, respectively. We used binary mixtures of cinnamaldehyde and eucalyptol, in different proportions presented as physical mixtures (the same exact mixture presented birhinally to each nostril) or as a dichorhinic mixtures (different mixtures presented to each nostril). Presenting dichorhinic mixtures allowed us to assess nostril dominance based on participants' report on whether the mixture smelled more like cinnamon or eucalyptus. Participants also evaluated whether the stimuli were "painful, " "warm, " "cold, " and "intense" on visual scales. Results: In Study 1, we find that in right handers, stimuli presented to the right nostril dominated over those presented to the left nostril. These stimuli were also rated as more "painful" and "intense." In Study 2, we could not corroborate the findings in the right-handed individuals, and we found limited support for a nostril advantage left-handed individuals. Conclusion: Although our data points toward a certain nostril advantage in chemosensory perception, the finding is not systematic, we discuss possible underlying factors.